Combined pesticide pollution enhances the dissemination of the phage-encoded antibiotic resistome in the soil under nitrogen deposition - Luo-Qin Shen; Da Lin; Yu-Qiu Ye; Yanjie Liu; Bang Ni; Di Wu; Lu Wang; Dong Zhu (Proceedings of the National Academy of Sciences, 2025)
Phage-mediated dissemination of antibiotic resistance genes (ARGs) intensifies health threat in the environment. Increasing amounts of pesticides are entering the soil ecosystem, yet their potential influence on phage-mediated ARG spread, particularly under conditions of global change, remains poorly understood. In this study, we performed a long-term field experiment simulating pesticide contamination under nitrogen deposition and examined the role of soil phages in ARG spread and host adaptation using metagenomic and viromic sequencing. Combined pesticide markedly elevated the abundance of phage-encoded ARGs under nitrogen deposition. By enhancing phage–host interactions and increasing the co-occurrence of auxiliary metabolic genes with ARGs, phages may further facilitate the transfer of ARGs to bacterial hosts, conferring hosts a competitive edge in intensified microbial competition driven by combined pesticide exposure under nitrogen deposition. The phage-driven mechanism was supported by in vitro cultivation experiments, demonstrating that phages harboring ARGs, shaped by long-term combined pesticide exposure under nitrogen deposition, can infect bacterial hosts and confer resistance. Collectively, our findings underscore the pivotal role of phages in ARG mobilization under environmental stressors, reinforcing the importance of accounting for phage activity in ARG risk assessments under global change.